The Relationship between Physical Activity Levels and Quality of Life in Menopausal Women - Guna, I Wayan Adi Wira; Andayani, Ni Luh Nopi; Ayu, I Gusti; Putra, I Putu Yudi Pramana (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Physiologically during menopause, women will experience a decrease in the function of the ovaries which causes a decrease in reproductive hormones and increased health problems that have an impact on their quality of life. In general, the quality of life of menopausal women is influenced by several aspects, one of which is the level of physical activity carried out daily. This study aimed to determine the relationship between physical activity level to quality of life in menopausal women. Methods: The method used in this research is observational analytics with a cross-sectional approach. The sampling technique used is purposive sampling. The number of samples obtained in this study was 69 samples. Data collection was done by measuring physical activity levels and quality of life. Physical activity levels were measured using the Global Physical Activity Questionnaire (GPAQ) while quality of life was measured by the World Health Organization Quality of Life Questionaire (WHOQOL-BREF). Result: Based on the non-parametric analysis test of Spearman rho, a value of p = 0.000 (p < 0.05) and a correlation coefficient r = 0.649. Conclusion: Based on the results of the study, it can be concluded that there is a significant relationship between the level of physical activity and menopausal women.